Differences between Risk Factors Associated with Tuberculosis Treatment Abandonment and Mortality - Gomes, Nathália Mota de Faria; Bastos, Meire Cardoso da Mota; Marins, Renata Magliano; Barbosa, Aline Alves; Soares, Luiz Clóvis Parente; de Abreu, Annelise Maria de Oliveira Wilken; Souto Filho, João Tadeu Damian (Pulmonary Medicine, 2015)
Objectives. To identify the risk factors that were associated with abandonment of treatment and mortality in tuberculosis (TB) patients. Methods. This study was a retrospective longitudinal cohort study involving tuberculosis patients treated between 2002 and 2008 in a TB reference center. Results. A total of 1,257 patients were evaluated, with 69.1% men, 54.4% under 40 years of age, 18.9% with extrapulmonary disease, and 9.3% coinfected with HIV. The risk factors that were associated with abandonment of treatment included male gender (OR = 2.05; 95% CI = 1.15–3.65) and nonadherence to previous treatment (OR = 3.14; 95% CI = 1.96–5.96). In addition, the presence of extrapulmonary TB was a protective factor (OR = 0.33, 95% CI = 0.14–0.76). The following risk factors were associated with mortality: age over 40 years (OR = 2.61, 95% CI = 1.76–3.85), coinfection with HIV (OR = 6.01, 95% CI = 3.78–9.56), illiteracy (OR = 1.88, 95% CI = 1.27–2.75), the presence of severe extrapulmonary TB (OR = 2.33, 95% CI = 1.24–4.38), and retreatment after relapse (OR = 1.95, 95% CI = 1.01–3.75). Conclusions. Male gender and retreatment after abandonment were independent risk factors for nonadherence to TB treatment. Furthermore, age over 40 years, coinfection with HIV, illiteracy, severe extrapulmonary TB, and retreatment after relapse were associated with higher TB mortality. Therefore, we suggest the implementation of direct measures that will control the identified risk factors to reduce the rates of treatment failure and TB-associated mortality.